Habitat and Nest Characteristics of Javan Hawk-eagle (Nisaetus bartelsi Stresemann 1924) in Gunung Salak 1 Resort Area of Gunung Halimun Salak National Park - Febryan , Febryan; Prihatini, Wahyu; Rahayu, Sata Yoshida Srie (Universitas Nasional Jakarta, 2024)
The Javan Hawk-eagle Nisaetus bartelsi is a protected bird of prey endemic to Java Island and is one of Indonesia's mascot fauna. The survival of this species in nature is threatened, among others due to habitat degradation, and land use change around its habitat. This study was conducted to analyze the presence and characteristics of nests and the habitat around Javan eagle nests in the Gunung Salak 1 Resort area within the Gunung Halimun Salak National Park. The research was conducted using the Direct Observation method, with parameters namely characteristics of nest trees, and nests, as well as biotic and abiotic environments around Javan eagle nests. The results found the presence of active Javan eagle nests in the Hameurang Valley block in the Sintok area, and the Curug Cibadak block in the Loji area. The nest in Sintok was found in a beunying tree (Ficus fistulosa) in a natural forest, at 1,097 m above sea level. Nests in Loji were found in rasamala (Altingia excelsa) trees in the natural forest, at 1,347 m asl. The nest is located at the height of 15-22 m from the ground, round in shape, the nest material is epiphytic plants, branches of puspa (Schima wallichii), rasamala (Altingia excelsa), and manii (Maesopsis eminii). The plant around the nest with the highest INP in Sintok is the manii tree (Maeopsis emini), while in Loji it is the seuhang tree (Ficus grossulariodes).